Well-defined polyester-grafted silica nanoparticles for biomedical applications: Synthesis and quantitative characterization. (21st December 2020) - Lagarrigue, Prescillia; Soulié, Jérémy; Grossin, David; Dupret-Bories, Agnès; Combes, Christèle; Darcos, Vincent
Abstract: Polyester-based composites with silica nanoparticles fillers are promising candidates as biomaterials due to improved mechanical and biological properties. However, nanofillers use generally leads to an inhomogeneous distribution inside the polymer matrix because of agglomeration, decreasing composites overall performances. In view of improving nanofillers dispersion, we developed a synthesis and characterization method to design poly(d, l -lactide)-grafted silica nanoparticles using "grafting to" method and to quantify the amount of grafted poly(d, l -lactide). Firstly, well-defined N -hydroxysuccinimide ester poly(d, l -lactide)s were synthesized through a new pathway. Then, amino-functionalized silica nanoparticles were grafted with those customized polyesters yielding an amide covalent bond between both reagents. Such PDLLA-grafted nanoparticles were precisely characterized and the grafting amount was quantified using a dual approach based on TGA and FTIR analysis. The synthesis and the characterization methods developed constitute a robust and reproducible way to design well-defined polymer-grafted silica nanoparticles that could be used as nanofillers in polymer matrix nanocomposites for biomedical applications. Graphical abstract: Image 1 Highlights: Synthesis of well-defined N -hydroxysuccinimide ester poly(d, l -lactide)s. Grafting of customized polyesters onto amino-silica nanoparticles. Polyester-grafted silica nanoparticles were designed through a new pathway. Grafting density was quantified by a dual approach based on TGA and FTIR analysis. We designed well-defined polymer-grafted silica nanoparticles as nanofillers.